Zelda and the maternal‐to‐zygotic transition in cockroaches. (30th April 2019) - Ventos‐Alfonso, Alba; Ylla, Guillem; Belles, Xavier
Abstract : In the endopterygote Drosophila melanogaster, Zelda is an activator of the zygotic genome during the maternal‐to‐zygotic transition (MZT). Zelda binds cis ‐regulatory elements (TAGteam heptamers), making chromatin accessible for gene transcription. Zelda has been studied in other endopterygotes: Apis mellifera and Tribolium castaneum, and the paraneopteran Rhodnius prolixus . We studied Zelda in the cockroach Blattella germanica, a hemimetabolan, short germ‐band, and polyneopteran species. B. germanica Zelda has the complete set of functional domains, which is typical of species displaying ancestral features concerning embryogenesis. Interestingly, we found D. melanogaster TAGteam heptamers in the B. germanica genome. The canonical one, CAGGTAG, is present at a similar proportion in the genome of these two species and in the genome of other insects, suggesting that the genome admits as many CAGGTAG motifs as its length allows. Zelda‐depleted embryos of B. germanica show defects involving blastoderm formation and abdomen development, and genes contributing to these processes are down‐regulated. We conclude that in B. germanica, Zelda strictly activates the zygotic genome, within the MZT, a role conserved in more derived endopterygote insects. In B. germanica, zelda is expressed during MZT, whereas in D. melanogaster and T. castaneum it is expressed beyond this transition. In these species and A. mellifera, Zelda has functions even in postembryonic development. The expansion of zelda expression beyond the MZT in endopterygotes might be related with the evolutionary innovation of holometabolan metamorphosis. Databases: The RNA‐seq datasets of B. germanica, D. melanogaster, and T. castaneum are accessible at the GEO databasesGSE99785, GSE18068, GSE63770, andGSE84253 . In addition, the RNA‐seq library from T. castaneum adult females is available at SRA: SRX021963. The B. germanica reference genome is available as BioProject PRJNA203136. Abstract : In flies ( Drosophila, complete metamorphosis), Zelda is expressed along the life cycle, activates the zygotic genome in early embryogenesis, and plays other roles during further development. In cockroaches ( Blattella, gradual metamorphosis), Zelda is expressed in the early embryo and only activates the zygotic genome. The expansion of Zelda expression beyond the maternal‐to‐zygotic transition might be related to the evolutionary innovation of complete metamorphosis.